Expert stakeholder perspectives on the acceptability of treatment‐as‐prevention in prison: a qualitative substudy of the 'Surveillance and Treatment of Prisoners with Hepatitis C' project (SToP‐C). (24th March 2021) - Rance, Jake; Lafferty, Lise; Treloar, Carla; ,
Abstract: Background and aims: Mathematical modelling has demonstrated the theoretical feasibility of HCV treatment‐as‐prevention strategies in custodial settings, yet limited empirical data exists. The Australian 'Surveillance and Treatment of Prisoners with Hepatitis C' study is the world's first trial of hepatitis C virus (HCV) treatment‐as‐prevention in prison. This study aimed to analyse how expert stakeholders involved in the Australian HCV response assessed the acceptability of HCV treatment‐as‐prevention in prison using interview data from the SToP‐C qualitative substudy. Design and setting: Qualitative analysis using semi‐structured interviews in Australia. Participants: Nineteen key HCV experts. Measurements: Drawing upon Sekhon's theoretical framework of acceptability, data were organized thematically under four component constructs of acceptability: affective attitude; ethicality; opportunity costs; and perceived effectiveness. Findings: Most differences in participant assessments of acceptability were a matter of relative emphasis and prioritization rather than absolute polarity. Nonetheless, a small minority of participants was overtly critical of the approach. Arguing against the focus on treatment, they instead advocated for prevention‐as‐prevention, including the improvement and expansion of existing harm reduction measures. Conclusions: Qualitative analysis of expert stakeholder assessments of the acceptability of hepatitis C virus treatment‐as‐prevention in Australian prisons found no opposition to the universal rollout of direct‐acting anti‐virals, but most voiced concern regarding the lack of effective primary prevention in Australian prisons.